Korean slang words. - Kadirbek. М. А. (Journal of Oriental Studies, 2016)
This paper is based on general characteristic of Korean slang words including the history of investigation of Korean slang words. In the field of Korean studies Korean slang words should be actively investigated to study Koreans’ way of thinking.